Inhaled Medicines for Targeting Non-Small Cell Lung Cancer - Arwa Omar Al Khatib; Mohamed El-Tanani; Hisham Al-Obaidi (MDPI AG, 2023)
Throughout the years, considerable progress has been made in methods for delivering drugs directly to the lungs, which offers enhanced precision in targeting specific lung regions. Currently, for treatment of lung cancer, the prevalent routes for drug administration are oral and parenteral. These methods, while effective, often come with side effects including hair loss, nausea, vomiting, susceptibility to infections, and bleeding. Direct drug delivery to the lungs presents a range of advantages. Notably, it can significantly reduce or even eliminate these side effects and provide more accurate targeting of malignancies. This approach is especially beneficial for treating conditions like lung cancer and various respiratory diseases. However, the journey towards perfecting inhaled drug delivery systems has not been without its challenges, primarily due to the complex structure and functions of the respiratory tract. This comprehensive review will investigate delivery strategies that target lung cancer, specifically focusing on non-small-cell lung cancer (NSCLC)-a predominant variant of lung cancer. Within the scope of this review, active and passive targeting techniques are covered which highlight the roles of advanced tools like nanoparticles and lipid carriers. Furthermore, this review will shed light on the potential synergies of combining inhalation therapy with other treatment approaches, such as chemotherapy and immunotherapy. The goal is to determine how these combinations might amplify therapeutic results, optimizing patient outcomes and overall well-being.